Bacillus glennii sp. nov. and Bacillus saganii sp. nov., isolated from the vehicle assembly building at Kennedy Space Center where the Viking spacecraft were assembled. Issue 1 (3rd February 2020) - Seuylemezian, Arman; Ott, Logan; Wolf, Sarah; Fragante, Jomel; Yip, Oscar; Pukall, Rüdiger; Schumann, Peter; Vaishampayan, Parag
Abstract : Two Gram-stain-positive, motile, endospore-forming, aerobic strains, designated V44-8 T and V47-23a T, were isolated from environmental air sampling at the vehicle assembly building at Cape Canaveral, Florida, where the Viking spacecraft were assembled. Growth was observed at pH 7–9 (optimum, pH 9) for strain V44-8 T, and pH 5–10 (pH 9) for strain V47-23a T . Both strains displayed growth in 0–5 % NaCl with an optimum at 1 % for strain V44-8 T ; 0 % for strain V47-23a T . Strains V44-8 T and V47-23a T grew optimally at 32 °C, (15–32 °C) and 25 °C (20–45 °C), respectively. The cell wall of both strains contained meso-diaminopimelic acid as the diagnostic diamino acid. Both strains contained phosphatidylglycerol, phosphatidylethanolamine and diphosphatidylglycerol. The predominant cellular fatty acids were anteiso-C15 : 0, iso-C14 : 0 and iso-C15 : 0 . Strain V47.23a T shared its highest 16S rRNA sequence similarity with Bacillus cavernae DSM-105484 T at 96.9%, and V44.8 T with Bacillus zeae DSM-103964 T at 96.6 %. Based on their phenotypic characteristics and phylogenetic position inferred from 16S rRNA gene sequence analyses, the isolates were identified as being a members of the genus Bacillus that forms a separate clade when compared to close relatives. Average nucleotide identity and average amino acid identity values between strains V44-8 T and DSM-103964 T were 72.1% and 67.5 %; V47-23a T and DSM-105484 T were 62.4% and 69.1%, respectively. Based on the phenotypic, genomic and biochemical data, strains V44-8 T and V47-23a T represent two novel species in the genus Bacillus for which the names Bacillus glennii sp. nov. [type strain, V44-8 T (=ATCC BAA-2860 T =DSM 105192 T )], and Bacillus saganii sp. nov. [V47-23a T (=ATCC BAA-2861 T =DSM 105190 T )] are proposed.